The Effectiviness of Soursop (Annona Muricatal) Leaves Decortion Water on the Leucorrhea - Santi Yulianti; Vivi Silawati; Febry Mutiariami Dahlan; Putri Azzahroh (Indonesian Journal of Global Health Research, 2024)
Garut Regency in 2021, women who experienced vaginal discharge were 318,976 or 29.73%. The high number of cases of vaginal discharge in women of childbearing age and the frequent occurrence of less serious treatment when vaginal discharge occurs are of particular concern among women. One way that can be done to treat vaginal discharge is to use a decoction of soursop leaves because they contain antiseptic substances that can kill germs, namely phenol, which has antiseptic properties 5 times more effective than ordinary phenol. Objective: To determine the effectiveness of soursop leaf decoction (Annona muricata L) on vaginal discharge in women of childbearing age in the Karangmulya Health Center Working Area, Garut Regency. Methodology: This study used a quasi-experimental pre-test-post-test with control design. The population in the study were all those who experienced leucorrhea with a score of >5 or 50 people. The sample in the study used total sampling which was divided into two groups, 25 respondents in the experimental group and 25 respondents in the control group. The instruments used were observation sheets and technical instructions about the use of soursop leaf decoction. Data analysis used the Wilcoxon and Mann Whitney tests. Results: The average score of vaginal discharge in the experimental group before the intervention was 10.32 and after the intervention was 6.84, while the average score in the control group in the first measurement was 10.36 and in the second measurement was 9.04. The bivariate results showed a p-value in the experimental group of 0.000, a p-value in the control group of 0.000 and a p-value comparison of the experimental and control groups of 0.000. Conclusion: Soursop leaf decoction has been proven effective in treating vaginal discharge in women of childbearing age, so there is a difference in vaginal discharge experienced by women of childbearing age after being given soursop leaf decoction between the experimental and control groups. Suggestion: It is hoped that women of childbearing age can handle or treat vaginal discharge independently by using soursop leaf decoction.